2021
DOI: 10.1021/acs.jafc.0c07597
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Enriched in Spinach and its Effects on Gut Microbiota

Abstract: Meat and fermented foods are the main source of vitamin B12 (cobalamin) for human beings. Therefore, daily cobalamin intake is a big problem for vegans. In this study, cyanocobalamin (CNCBL) was added to the culture broth for cobalamin enrichment in spinach. After 36 h of cultivation, the accumulated CNCBL in the spinach leaves (wet weight) was as high as 0.48% (concentration), and the leaves still contained 0.94 ± 0.11 μg/g CNCBL after boiling, which could provide consumer daily requirement of CNCBL. Because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In vitro study suggested that the addition of cobalamins increases the generation of SCFAs, especially butyrate and propionic acid ( 218 ). Another in vitro study indicated that low-dose cyanocobalamin-enriched spinach could increase the generation of butyrate and acetate ( 228 ). In mice, a reduction of SCFAs has been observed in dietary vitamin B12 restriction ( 229 ).…”
Section: Vitamin B12mentioning
confidence: 99%
“…In vitro study suggested that the addition of cobalamins increases the generation of SCFAs, especially butyrate and propionic acid ( 218 ). Another in vitro study indicated that low-dose cyanocobalamin-enriched spinach could increase the generation of butyrate and acetate ( 228 ). In mice, a reduction of SCFAs has been observed in dietary vitamin B12 restriction ( 229 ).…”
Section: Vitamin B12mentioning
confidence: 99%
“…Recent human clinical intervention trials have assessed diverse aspects of SPI intake, including anthropometric measures, muscle fitness, metabolic profiles, arterial stiffness, and urinary biomarkers [5,[34][35][36], extending prior research on the health benefits of green leafy vegetables and the functional properties of spinach-derived phytochemicals and bioactives [37][38][39][40][41]. We reported that long-term feeding of freeze-dried SPI at 10% w/w in the diet for 26 weeks exhibited significant antitumor efficacy in the Pirc model, resulting in >60% reduced tumor multiplicity in the colon and small intestine [6].…”
Section: Discussionmentioning
confidence: 99%
“…Detection conditions: column—ZORBAX SB-Aq (4.6 × 250 mm 5-micron); mobile phase—0.025% phosphate aqueous solution (pH = 2.8), acetonitrile = 95:5; flow rate—1.0 mL/min; injection volume—20 μL; detection wavelength—210 nm; column temperature—30 °C [ 10 ].…”
Section: Methodsmentioning
confidence: 99%